2022
DOI: 10.3389/fimmu.2022.871756
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination repair gene mutations as a predictive biomarker for immunotherapy in patients with advanced melanoma

Abstract: BackgroundNowadays, immunotherapy targeting immune checkpoint receptors is one of the cornerstones of systemic treatment in melanoma. Homologous recombination repair (HRR) is one of the DNA damage response (DDR) pathways, which has been proved to correlate with the efficacy of platinum-based chemotherapy, PARP inhibitor therapy, and immunotherapy in a variety of cancers. However, their predictive value of HRR remained unknown in patients with advanced melanoma.MethodsData of advanced melanoma patients from an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Recently, an observational study enrolling 266 patients with non‐small cell lung cancer showed similar results 44 . Moreover, a previous study analyzed several public cohorts and showed that patients with HRR mutations had better outcomes after anti‐CTLA‐4 treatment in advanced melanoma 45 . However, the predictive value of HRR mutations for immunotherapeutic response in UC remains unknown.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recently, an observational study enrolling 266 patients with non‐small cell lung cancer showed similar results 44 . Moreover, a previous study analyzed several public cohorts and showed that patients with HRR mutations had better outcomes after anti‐CTLA‐4 treatment in advanced melanoma 45 . However, the predictive value of HRR mutations for immunotherapeutic response in UC remains unknown.…”
Section: Discussionmentioning
confidence: 83%
“… 44 Moreover, a previous study analyzed several public cohorts and showed that patients with HRR mutations had better outcomes after anti‐CTLA‐4 treatment in advanced melanoma. 45 However, the predictive value of HRR mutations for immunotherapeutic response in UC remains unknown. Our analysis revealed that patients with HRR mutations, especially those with ATM mutations, had improved overall survival than those without HRR mutations after immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…MSI is a marker for ICI treatment; however, only ∼53% of MSI cases have an objective response to ICI treatment 119 , suggesting additional biomarkers are necessary to stratify MSI cases. Several biomarkers have been proposed for ICI treatment, including HRD 120 , ARID1A LOF121 , and SETD2 LOF122 . Wang et al 123 also demonstrated that mice transplanted with KMT2D-deficient tumours were responsive to ICI treatment and that TMB was elevated in TCGA cases with KMT2D LOF .…”
Section: Discussionmentioning
confidence: 99%
“…In view of the high frequency of DDR deficiency in tumorigenesis and progression, extensive efforts have been made to identify DDR-related biomarkers for predicting the response to ICI therapy. Several investigations have demonstrated that gene mutations in different DDR pathways result in a durable clinical benefit from ICI therapy in various types of cancer, including melanoma 34 , lung cancer 35 , bladder cancer 19 , and GI cancer 20 . Previous studies, however, have also shown that even though BRCA1/2 mutations may confer sensitivity to ICI therapy, this is not held in common for all patients because not all mutations induce DDR deficiency or compensate for by alternate mechanisms 36 .…”
Section: Discussionmentioning
confidence: 99%